Environmental change in sustainable management approach in Brazilian public education: Multiple case study (2020)
This work aimed to study the Environmental Agenda in Public Administration - A3P in two public institutions in Brazil: Federal Institute of Tocantins - IFTO and Technological Education Federal Center - Cefet/RJ. A3P implementation is intended to insert an Environmental Management system, mitigating risks of loss in public assets and natural resources waste. In addition, it proposes new management approach encouraging environmental education. Environmental Agenda in Public Administration - A3P encourages Civil Servants to embody environmental management principles in their daily activities saving natural resources, reducing public spending through the more rational use of public goods and proper residues management. This work can contribute as a source of information about topic, whose publications still are scarce in the country, thereby encouraging the adoption of A3P in other Brazilian public institutions.